Analysis of Competitiveness in the NBA Regular Seasons - Yves de Saá Guerra; Juan Manuel Martín González; Nieves Arjonilla López; Samuel Sarmiento Montesdeoca; David Rodríguez Ruiz; Juan Manuel García Manso (Lithuanian Sports University, 2018)
Research background and hypothesis. Several attempts have been made to understand some modalities of sport from the point of view of complexity. Most of these studies deal with this phenomenon with regard to the mechanics of the game itself (in isolation). Nevertheless, some research has been conducted from the perspective of competition between teams. Our hypothesis was that for the study of competitiveness levels in the system of league competition our analysis model (Shannon entropy), is a useful and highly sensitive tool to determine the degree of global competitiveness of a league. Research aim. The aim of our study was to develop a model for the analysis of competitiveness level in team sport competitions based on the uncertainty level that might exist for each confrontation. Research methods. Degree of uncertainty or randomness of the competition was analyzed as a factor of competitiveness. It was calculated on the basis of the Shannon entropy. Research results. We studied 17 NBA regular seasons, which showed a fairly steady entropic tendency. There were seasons less competitive (≤ 0.9800) than the overall average (0.9835), and periods where the competitiveness remained at higher levels (range: 0.9851 to 0.9902). Discussion and conclusions. A league is more competitive when it is more random. Thus, it is harder to predict the ﬁ nal outcome. However, when the competition is less random, the degree of competitiveness will decrease signiﬁ cantly. The NBA is a very competitive league, there is a high degree of uncertainty of knowing the ﬁ nal result. Keywords: complex systems, basketball, entropy, competition, randomness.